2019
DOI: 10.1016/j.optcom.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling domain switching of ferroelectric BaTiO3 integrated in silicon photonic waveguides

Abstract: A B S T R A C TWe present a model to investigate the local change of the refractive index of a ferroelectric material employed as upper cladding of silicon photonic waveguides. The model is used to predict the saturation voltage required to achieve complete domain switching in case of a BaTiO 3 film and to evaluate the performance of non-volatile phase-actuators integrated in silicon waveguides. Results show that the refractive index change associated with the domain switching of the BaTiO 3 cladding enables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Voltage dependence of coupling length appears through the variation of change in n of BTO with applied bias. The variation in n is simulated using a semi-empirical model reported in ref [29]. Using that study, the coercive field of BTO cladding is found to be 27.7 kV/cm, for a cladding thickness of t = 1000 nm.…”
Section: B Estimation Of Transverse Dimensionmentioning
confidence: 99%
“…Voltage dependence of coupling length appears through the variation of change in n of BTO with applied bias. The variation in n is simulated using a semi-empirical model reported in ref [29]. Using that study, the coercive field of BTO cladding is found to be 27.7 kV/cm, for a cladding thickness of t = 1000 nm.…”
Section: B Estimation Of Transverse Dimensionmentioning
confidence: 99%
“…1(a)) in two biasing configurations, say "biasing-1" (to set n to ne) and "biasing-2" (to set n to no) (Fig. 1(c)) as reported earlier [28,36]. Initially n is taken as no.…”
Section: Schematic Structure With Proposed Designmentioning
confidence: 99%
“…[22][23][24][25][26]. It's refractive index (n) varies from 2.41 (no) to 2.36 (ne) tracing the orientation of its ferroelectric domains from in-plane (a-axis) to out-of-plane (c-axis) with application of suitable amount of electric field [27,28]. This huge modulation (i.e., Δn = 0.05) is fast (takes few tens of microseconds) and quite non-volatile in nature [29][30][31].…”
mentioning
confidence: 99%
“…Ferroelectrics hold the promise to revolutionize low‐power logic, nonvolatile memories, actuators, sensors, and electro‐optics for waveguide devices. [ 1–24 ] These applications require suitable control and manipulation of ferroelectric domains and domain walls in ferroelectric thin films. Since 180° polarization switching was accomplished in 4.8 nm thick tetragonal BaTiO 3 thin films via mechanical manipulation, [ 25 ] considerable effort has been devoted to manipulating the polarization switching in ferroelectric thin films, for example, 3–5 nm thick PbZr 0.2 Ti 0.8 O 3 (001) film, 1.6–45 nm thick BaTiO 3 (001) film, 50 nm thick PbZr 0.1 Ti 0.9 O 3 (001) film, and 10 nm thick PbZr 0.48 Ti 0.52 O 3 (001) film, and flexoelectric effect is proposed to explain the mechanical manipulation of the domain and domain wall structures.…”
Section: Introductionmentioning
confidence: 99%